Study Regarding the Accounting and Taxation of Exploration for and Evaluation of Mineral Resources - Cristina NICOLAESCU (CECCAR Business Review, 2021)

(untitled)
Considering the particular and special nature of the activity of exploitation of mineral resources undertaken both underground (mines) and on the surface (ballasts/quarries), this article aims is to analyse the specific legal and fiscal aspects related to this activity, as well as the specific accounting procedures involved. To this end, the article summarizes the main regulatory acts governing the activity of exploration and exploitation of mineral resources from a legal and fiscal point of view. Another purpose of the paper is to provide solutions to account for the economic operations specific to these activities based on an international experience in this field.